Determinants of Logistics Distribution Efficiency: A Case Study in Alor District, East Nusa Tenggara - Jakfar (Indonesian Scientific Publication, 2024)
Indonesia’s remote regions face persistent logistical challenges due to geographic fragmentation, infrastructure deficits, and limited digital adoption. This study examines the determinants of logistics distribution efficiency in Alor District, East Nusa Tenggara, using survey data from 150 respondents including logistics operators, government officials, and recipients. Descriptive and inferential analyses, including correlation and multiple linear regression, reveal that logistics information technology is the most influential factor (r = 0.71; β = 0.35), followed by infrastructure quality (r = 0.62; β = 0.28) and supply chain coordination (r = 0.55; β = 0.22), all significant at p < 0.05. These findings highlight the critical role of digital transformation in improving distribution efficiency in archipelagic regions. Practical recommendations include expanding internet connectivity in rural islands, providing digital literacy training for logistics actors, and developing integrated coordination platforms at the district level. Limitations of this study include reliance on self-reported data, potential non-response bias, and the focus on a single district, which may affect generalizability. Future research should incorporate longitudinal data and cross-district comparisons to strengthen evidence on logistics innovation in remote areas.